Influences of Patellofemoral Pain and Fatigue in Female Dancers during Ballet Jump-Landing - Peng, H.-T.; Chen, W. C.; Kernozek, T. W.; Kim, K.; Song, C.-Y. (International Journal of Sports Medicine, 2015)
This study investigated the influence of patellofemoral pain (PFP) and fatigue on lower-extremity joint biomechanics in female dancers during consecutive simple ground échappé. 3-dimensional joint mechanics were analyzed from the no-fatigue to fatigue conditions. 2-way mixed ANOVAs were used to compare the differences of the kinematic and kinetic variables between groups and conditions. Group main effects were seen in increased jump height (p=0.03), peak vertical ground reaction force (p=0.01), knee joint power absorption (p=0.04), and patellofemoral joint stress (PFJS, p=0.04) for PFP group. Fatigue main effects were found for decreased jump height (p<0.01), decreased ankle plantarflexion at initial foot-ground contact (p=0.01), and decreased ankle displacement (p<0.01). Hip external rotation impulse and hip joint stiffness increased (both p<0.01) while knee extension and external rotation moment, and ankle joint power absorption decreased (p<0.01, p=0.02, p<0.01, respectively) after fatigue. The peak PFJS also decreased after fatigue (p<0.01). Female ballet dancers with PFP sustained great ground impact and loads on the knee probably due to higher jump height compared to the controls. All dancers presented diminished knee joint loading for the protective mechanism and endurance of ankle joint musculature required for the dissipation of loads and displayed a distal-to-proximal dissipation strategy after fatigue.
Keywords: repetitive jumping; impact force; stiffness; PFP; dance; patellofemoral joint stress